2015
DOI: 10.1186/s13021-014-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide fluxes from contrasting ecosystems in the Sudanian Savanna in West Africa

Abstract: BackgroundThe terrestrial land surface in West Africa is made up of several types of savanna ecosystems differing in land use changes which modulate gas exchanges between their vegetation and the overlying atmosphere. This study compares diurnal and seasonal estimates of CO2 fluxes from three contrasting ecosystems, a grassland, a mixture of fallow and cropland, and nature reserve in the Sudanian Savanna and relate them to water availability and land use characteristics.ResultsOver the study period, and for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 51 publications
9
69
0
5
Order By: Relevance
“…This was probably due to the differences between the soil evaporation rates, soil characteristics, deeps infiltration, and importance of the runoffs in relation with the vegetation types at the two sites. These results were in accordance with other findings reported between some sites more and less near each other in West Africa by other authors, especially concerning the rainfall regimes (Ago et al 2005;Boulain et al 2009;Seghieri et al 2009;Merbold et al 2009;Quansah et al 2015). It appears reasonable to consider both meteorological conditions at the two sites as similar overall.…”
Section: Micro-meteorological Conditionssupporting
confidence: 83%
See 4 more Smart Citations
“…This was probably due to the differences between the soil evaporation rates, soil characteristics, deeps infiltration, and importance of the runoffs in relation with the vegetation types at the two sites. These results were in accordance with other findings reported between some sites more and less near each other in West Africa by other authors, especially concerning the rainfall regimes (Ago et al 2005;Boulain et al 2009;Seghieri et al 2009;Merbold et al 2009;Quansah et al 2015). It appears reasonable to consider both meteorological conditions at the two sites as similar overall.…”
Section: Micro-meteorological Conditionssupporting
confidence: 83%
“…This suggests that the ER was mainly controlled by the soil water availability at the two sites as reported for similar ecosystems in Africa by other authors (Williams and Albertson 2004;Williams et al 2009;Ago et al 2014). In contrast, other studies reported for several dry West African sites (annual sum rainfall < 1000 mm) that the ER was primarily driven by the temperature and additionally by the soil water content (Brümmer et al 2008;Merbold et al 2009;Quansah et al 2015). The uncertainties are the 95 % confidence intervals T A air temperature, T S soil temperature, VPD vapor pressure deficit, SWC soil water content at 10 cm depth, LAI leaf area index, F forest, S savannah…”
Section: Diurnal Patterns Of Co 2 Fluxes and Driving Factorsmentioning
confidence: 80%
See 3 more Smart Citations